The Judge's Ex Officio Authority in Fulfilling Wife and Child Support Rights After Divorce in the Religious Court: Kewenangan Ex Officio Hakim dalam Pemenuhan Hak Nafkah Istri dan Anak Pasca Perceraian di Pengadilan Agama - Dian Maulidah; Moh. Muhibbin; Diyan Isnaeni (Academia Open, 2027)
General Background Divorce generates continuing economic obligations toward former wives and children, making postdivorce maintenance a central concern in religious court proceedings. Specific Background Indonesian judges may exercise ex officio authority to determine maintenance even when it is not expressly requested, provided legal requirements and trial facts support such intervention. Knowledge Gap Previous studies have predominantly emphasized normative foundations and judicial authority, while empirical evidence concerning courtroom application, maintenance determination, implementation constraints, and the roles of judicial actors remains limited. Aims This empirical legal study examines the implementation of ex officio judicial authority in fulfilling postdivorce maintenance rights at the Malang Regency Religious Court and identifies factors shaping its application through a socio-legal approach, interviews, documentation, and legal literature. Results Ex officio authority functions as a legal protection mechanism based on trial facts, the husband’s economic capacity, the needs of former wives and children, proportionality, and child welfare. Its implementation is shaped by legal awareness, evidence of economic capacity, mediation, and judgment enforcement. Novelty The study proposes an integrated strengthening model comprising normative foundations, evidentiary reinforcement, procedural reinforcement, and judgment enforcement. Implications Religious courts should strengthen fact-finding capacity, legal aid services, mediation, and interinstitutional coordination to support the actual realization of maintenance entitlements after divorce. Highlights: Four implementation determinants emerged: legal awareness, proof of husbands’ economic capacity, mediation, and judgment enforcement. Awards depend on courtroom facts, financial ability, claimant needs, proportionality, and child welfare considerations. The proposed model integrates normative grounding, evidentiary quality, procedural coordination, and execution of decisions. Keywords: Ex Officio Judge, Maintenance Rights, Divorce.